PENGARUH PENYULUHAN METODE CERAMAH DALAM MENINGKATKAN PENGETAHUAN MASYARAKAT TERHADAP PENYAKIT TUBERKULOSIS - Safari Wahyu Jatmiko; Fitka Romanda; Muhammad Alim Abdulmajid Hidayatulloh (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2018)
Number of patients with tuberculosis (TB) in the region of Surakarta ranked 10th largest in the Central Java, although the government has already implemented the DOTS strategy. One factor contributing to the high number of TB patients is the lack of public knowledge of TB. The population of the city of Surakarta is 552.650 inhabitants and 12.480 of them live in Kalurahan Jagalan. Of the 12,480 people, nearly 60 percent of them have junior high school education. This requires education about TB to improve people's understanding of TB. Increased public knowledge of TB is expected to decrease the number of TB patients in Surakarta. The easiest education is with an interactive lecture method tailored to the level of participants' education. To ensure the achievement of the objectives of this activity then evaluated the improvement of public knowledge by providing questions before and after education.